Ablative properties and mechanisms of hot vulcanised silicone rubber (HVSR) composites containing different fillers. (25th November 2016) - Liu, Y.; Ma, C.; Li, Y.; Yin, Z.; Zhi, Y.; Gao, J.
Abstract : Hot vulcanised silicone rubber (HVSR) composites were prepared using silicon carbide (SiC), hafnium oxide (HfO2 ), zirconium oxide (ZrO2 ) and zirconium boride (ZrB2 ) as fillers, respectively. The tensile properties and the ablative response of the composites were examined. Tensile tests indicated that the tensile strength of HVSR was increased by the incorporation of ZrB2 . The linear ablation rate of the composites increased in the order HVSR/ZrB2  < HVSR/ZrO2  < HVSR/SiC < HVSR/HfO2  < blank HVSR. The maximum back-face temperatures of the composites acquired from the burnt specimens during the ablation test were 350 and 364 K for the HVSR/ZrB2 and HVSR/ZrO2, respectively, compared to that of 333 K for the blank HVSR. Scanning electron microscopy and X-ray diffraction results showed that the dense and rigid ceramic layer was hard to peel off under the high pressure and shearing forces of ablative gases. The HVSR/ZrB2 specimens exhibited the best ablation resistance among all the composites involved in this work.